Criteria for choice of treatment and diagnosis of combined chest injuries in children (Herald of the National Children's Medical Center, 2025)
Background. To analyze the features, advantages and disadvantages of integrated methods and systems used to assess the severity of community-acquired pneumonia.Materials and methods. This review is devoted to the study of the most common methods for assessing the severity of community-acquired pneumonia in patients. The article discusses the use of integrated assessment systems for forecasting and diagnosis in pediatrics, including young children. This is aimed at improving the results of diagnosis and treatment of patients with community-acquired pneumonia in both global and domestic healthcare practice.Results. Currently, several scales have been developed and proposed, but the most popular of them are the scales of the pneumonia severity index PSI (Pneumonia Severity Index) and CURB (Confusion, Urea, Respiratory rate, Blood). There are also a number of scales that have not been widely implemented in practice, such as the American Thoracic Society scale, the Australian SMART-COP scale, the Spanish CURXO-80 scale and the Japanese A-DROP scale, which are used to determine the severity of community-acquired pneumonia.Conclusion. As a result of the analysis, it was found that in order to improve the early diagnosis of community-acquired pneumonia, it is necessary to continue research in this area, develop new methods and approaches, and train medical personnel in modern standards of diagnosis and treatment, which will reduce morbidity and mortality among children.
Keywords: pneumonia; community-acquired pneumonia; scale; respiratory failure; children; early age; integral assessment; severity assessment